Establishment of a non‐integrated induced pluripotent stem cell line derived from human chorionic villi cells. Issue 6 (9th May 2022) - Long, Ping; Shi, Yuechuan; Sun, Fei; Wei, Yunjian; Wu, Bangyong; Li, Qi; Jie, Qiuling; Ma, Yanlin
Abstract: Background: Few studies have investigated the generation of induced pluripotent stem cells (iPSCs) derived from human primary chorionic villi (CV) cells. The present study aimed to explore an optimal electroporation (EP) condition for generating non‐integrated iPSCs from CV cells (CV‐iPSCs). Methods: The EGFP plasmid was transfected into CV cells under different EP conditions to evaluate cell adherence and the rate of EGFP positive cells. Subsequently, CV cells were transfected with the pEP4‐E02S‐ET2K and pCEP4‐miR‐302–367 plasmids under optimal EP conditions. Finally, CV‐iPSC pluripotency, karyotype analysis, and differentiation ability were investigated. Results: Following EP for 48 h under different conditions, different confluency, and transfection efficiency were observed in CV cells. Higher cell density was observed in CV cells exposed to 200 V for 100 s, while higher transfection efficiency was obtained in cells electroporated at a pulse of 300 V for 300 s. To generate typical primitive iPSCs, CV cells were transfected with pEP4‐E02S‐ET2K and pCEP4‐miR‐302–367 plasmids using EP and were then cultured in induction medium for 20 days under selected conditions. Subsequently, monoclonal iPSCs were isolated and were evaluated pluripotency with AP positive staining, the expression of OCT4, SOX2, and NANOG in vitro and the formation of three germ layer teratomas in vivo. Conclusion: CV‐iPSCs were successfully established under the conditions of 100 μl shock cup and EP pulse of 200 V for 300 s for two times. This may provide a novel strategy for investigating the pathogenesis of several diseases and gene therapy. Abstract : CV‐iPSCs have pluripotency both in vitro and in vivo. (A) Cell morphology during the induction of iPSCs from CV cells. (B) The expression of pluripotent marker OCT4, SSEA4, TRA‐1–60, and TRA‐1–81 in CV‐iPSCs by immunofluorescence staining (×1000). DAPI stained the nucleus (Blue). (C) Teratoma formation of CV‐iPSCs. Left: the view of mice anatomy. Right: the HE staining of typical cells of three germ layers endoderm, mesoderm, and ectoderm, respectively (×100).